Contemporary approaches to the diagnosis of hyperprolactinemia - О. А. Бурка; Т. М. Тутченко (Publishing House TRILIST, 2019)
Hyperprolactinemia (HP) is a persistent prolactin increase in serum. HP is a common endocrinopathy that impairs reproductive function, long term HP may lead to the metabolic disorders and a decrease in bone mineral density. Prolactin increase may be result of many physiological and pathological conditions, the diagnosis of which directly affects treatment approaches. Evaluation of prolactin is not only the basis for the HP diagnosis but also an indirect indicator of its cause. For this reason it is important to recognize the possible difficulties in the HP diagnosis associated with the following factors: pulsate nature of prolactin secretion; sensitivity to various exogenous and endogenous factors; presence of various molecular prolactin forms (macroprolactinemia) and rare laboratory artifacts (hook effect). Laboratory studies are also used to evaluate other endocrinopathies that can be the primary HP cause (hypothyroidism) or coexisting conditions (mixed pituitary adenomas, polycystic ovary syndrome). Stress-induced HP has to be differentiated from physiological HP via repeated prolactin tests is gaining increasing clinical importance. The article provides an overview of modern research and relevant clinical guidelines for the diagnosis of various HP causes and offers an algorithmic approach for this clinical problem, the main principles are: to exclude iatrogenic causes, pregnancy and hypothyroidism at the initial stage of diagnosis; in the absence of neuroophthalmic symptoms and prolactin levels under 50-80 ng/ml repeated prolactin testing may be necessary to exclude physiological HP; screening for macroprolactinemia in all cases of prolactin level under of 200 ng/ml allows diagnosing macroprolactinemia or non-functioning pituitary adenoma; if MRT shows on macroprolactinoma and/or there are neuroophthalmic symptoms in combination with a normal or slightly elevated prolactin level it is necessary to exclude possible hook effect; in order to exclude mixed pituitary adenomas based on clinical features it is necessary to evaluate growth hormone, insulin-like growth factor 1, adrenocorticotrophic and thyroid-stimulating hormones in addition to prolactin